South Africa’s Military Deployment to Northern Mozambique: Lessons from the United States of America’s (Mis)Adventure in Afghanistan - Adebayo, Joseph (Scientia Militaria - South African Journal of Military Studies, 2023)
In mid-2021, the government of South Africa deployed troops from the South African National Defence Force to the troubled Northern Province of Mozambique as part of a Southern African Development Community regional force to quell the threat posed by insurgents in the country. Poignantly, the deployment happened at about the same time the United States of America completed the withdrawal of its troops from Afghanistan after twenty years of military intervention. Shortly after the departure of the American troops, Afghanistan degenerated into anarchy with the takeover of government machinery by the Taliban, bringing to the fore years of discourse on the sustainability of military interventions. Scholars have adduced many reasons for the American “failure” in Afghanistan. One of the most prominent reasons was the failure of American policymakers to understand the role of tribe, religion, and ethnicity in conflict dynamics. Although the socio-political, socioeconomic, and sociocultural contexts of the South African intervention in Mozambique differ from the American context, there are lessons South Africa could learn to avoid some pitfalls. Employing secondary data, the study on which this article is based, examined the 20-year military American involvement in Afghanistan to proffer possible lessons for the involvement of the South African government in Mozambique.